Bank competition, real investment return and corporate financialization - Yihuan Mao; Nan Xu (China Journal of Accounting Studies (CJAS), 2024)
The competition and interaction between the financial and real industry transmitted to the micro level are manifested in the allocation trade-off between financial and non-financial assets of companies. However, little literature has discussed the role of financial intermediaries in corporate financialization. Using samples from China's A-share non-financial and non-real estate listed companies, we distinguish two competing hypotheses, the Reservoir hypothesis and the Profit-seeking hypothesis. We find that bank competition intensifies corporate financialization driven by profit-seeking motivation. This effect is strengthened in firms with a lower return on non-financial investments, greater market arbitrage space, or private ownership. Finally, economic consequences analysis suggests that bank competition enhances the crowding out effect of corporate financialization on real investments. This article focuses on the potential costs brought by financial competition and provides empirical evidence for our in-depth understanding of the relationship between the evolution of financial system and the financial asset allocation of micro-enterprises.
Keywords: 650; Bank competition; financialization; profit-seeking hypothesis; reservoir hypothesis